ANALISIS SEGMENTASI PASAR PRODUK ROKOK MILD BERDASARKAN ATRIBUT PRODUK DI KABUPATEN JEMBER - Alfian, Muhamad Ayson Teguh; Sudaryanto, Sudaryanto (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: The aims of this research were to analyze: (1) the market segmentation of Mild cigarette based on its attributes; (2) the kind of Mild cigarette product for every segment; (3) the kind of Mild cigarette that preferred by the most consumers; (4) the kind of attributes as the market differentiation of Mild cigarettes. This study analyzed 105 respondents of Mild cigarette consumers. Data were analyzed using statistical cluster and discriminant analysis. Results showed that: (1) the Mild cigarette’s consumers were divided into two segments, the first (the less selective) was consumers who did not consider the product’s attributes and the second (the selective ones) was consumers who considered the product’s attribute; (2) LA Mild, GG Mild, and A Mild had a similar position in consumers’ mind;(3) LA Mild could be accepted at every segment; (4) the product attributes differentiating the cigarette segments in Jember were brands, packaging, price, taste, tar and nicotine, and aroma. Price was the most important attribute among the Mild cigarette consumer segments in Jember. Keywords: Brand, Packaging, Price, Taste, Aroma, Tar and Nicotine.